Modeling of Myotonic Dystrophy Cardiac Phenotypes in Drosophila - Chakraborty, Mouli; Llamusi, Beatriz; Artero, Ruben (Frontiers in Neurology, 2018)
After respiratory distress, cardiac dysfunction is the second most common cause of fatality associated with the myotonic dystrophy (DM) disease. Despite the prevalance of heart failure in DM, physiopathological studies on heart symptoms have been relatively scarce because few murine models faithfully reproduce the cardiac disease. Consequently, only a small number of candidate compounds have been evaluated in this specific phenotype. To help cover this gap Drosophila combines the amenability of its invertebrate genetics with the possibility of quickly acquiring physiological parameters suitable for meaningful comparisons with vertebrate animal models and humans. Here we review available descriptions of cardiac disease in DM type 1 and type 2, and three recent papers reporting the cardiac toxicity of non-coding CUG (DM1) and CCUG (DM2) repeat RNA in flies. Notably, flies expressing CUG or CCUG RNA in their hearts developed strong arrhythmias and had reduced fractional shortening, which correlates with similar phenotypes in DM patients. Overexpression of Muscleblind, which is abnormally sequestered by CUG and CCUG repeat RNA, managed to strongly suppress arrhythmias and fractional shortening, thus demonstrating that Muscleblind depletion causes cardiac phenotypes in flies. Importantly, small molecules pentamidine and daunorubicin were able to rescue cardiac phenotypes by releasing Muscleblind from sequestration. Taken together, fly heart models have the potential to make important contributions to the understanding of the molecular causes of cardiac dysfunction in DM and in the quick assessment of candidate therapeutics.